Crack modeling of bituminous materials using extrinsic nonlinear viscoelastic cohesive zone (NVCZ) model. (20th April 2019) - Rodrigues, Julia Amaral; Teixeira, Jamilla Emi Sudo Lutif; Kim, Yong-Rak; Little, Dallas N.; Souza, Flavio V.
Highlights: An extrinsic nonlinear viscoelastic cohesive zone (NVCZ) model was presented. NVCZ model parameters were identified using an integrated experimental-numerical procedure. Fracture behavior of two fine aggregate matrix (FAM) were assessed to demonstrate the modeling. Model validation results showed the capability and efficacy of NVCZ modeling approach employed. Abstract: Cohesive zone modelling (CZM) has been used to model complex fracture process of various materials including bituminous materials. Among various CZM methods, this study used an extrinsic nonlinear viscoelastic cohesive zone (NVCZ) model implemented in a finite element method to efficiently predict nonlinear-inelastic fracture behavior of bituminous materials from crack nucleation, initiation, and propagation to complete failure. To examine the extrinsic NVCZ model, two fine aggregate matrix (FAM) bituminous mixtures with different fillers were evaluated experimentally and compared with the model's numerical results. Laboratory tests were performed to obtain model inputs and outputs, and a parametric analysis of the NVCZ model was conducted to investigate the influence of each model parameter in the FAM fracture process. Linear viscoelastic properties were obtained using dynamic frequency sweep tests, and NVCZ model parameters were identified using an integrated experimental-numerical calibration procedure that employed semicircular bending (SCB) tests and finite element simulations. To validate the model, the experimental and numerical simulation results of an indirect tensile (IDT) test were compared. The numerical modeling results agreed well with the laboratory testing results. The outcomes of this study suggest that the extrinsic NVCZ model can be an efficient tool to predict the highly nonlinear and viscoelastic fracture processes of binding constituents in bituminous materials.